Identification of key elements in MRI reporting of intracranial meningiomas based on a nationwide survey of clinical experts in Germany - Torge Huckhagel; Tammam Abboud; Jan Regelsberger; Stefan Rieken; Christian Riedel (Scientific Reports)
Abstract While MRI has become the imaging modality of choice for intracranial meningiomas, no radiologic reporting guidance exists to date that relies on a systematic collection of information relevant to the core medical disciplines involved in the management of these patients. To address this issue, a nationwide expert survey was conducted in Germany. A literature-based catalog of potential reporting elements for MRI examinations of meningioma patients was developed interdisciplinarily. Subsequently, all board-certified members of the German Societies of Neuroradiology, Neurosurgery and Radiation Oncology with expertise in managing meningioma patients were invited to vote on the relevance of the suggested items via online survey. A total of 150 experts participated in the study (104 neurosurgeons/radiation oncologists, 46 neuroradiologists). The reporting elements of tumor location, extent, growth pattern, contrast uptake, associated cysts, and impact on adjacent anatomic structures received widespread approval (> 75.0% of all participants). In addition, a vast majority (> 75.0%) supported reference to perifocal edema, signs of mass effect, and hydrocephalus. Postoperative imaging is particularly requested to describe the extent of resection (94.0%) and treatment-related changes (89.3%). Advanced methods (diffusion, perfusion, proton spectroscopy) and meningioma-specific classifications (Nauta, Zee, Sindou) were judged to be less relevant (< 50.0% agreement) to MRI reporting. To serve as a vital clinical communication tool and enable an optimal contribution to the care of meningioma patients, the radiological report should focus on the fundamental information requirements of the neuro-oncology treatment team encompassing primarily tumor location, extent, tissue imaging characteristics, and potential impairment of neighboring anatomical structures.